(untitled) (World Bulletin of Management and Law, 2022)
This article mainly considers the effect of cyber theft and data theft and its effect to the digital inheritance and analyses its consequences. However, this article considers the problems of electronic wills, which are the barriers to implement electronic wills instead of in a traditional, paper format. The implementation of digital inheritance combined with increasing proportion of cyber-attacks. To protect digital inheritance, cyber security issues are essential on this article. Finally, article concerns the current situation in Uzbekistan and what measures must be done.